ARTISTIC AND CREATIVE ACTIVITIES IN WORKING WITH PRESCHOOL CHILDREN - Irina Saraieva (Borys Grinchenko Kyiv Metropolitan University, 2021)
The development of children's creativity is an urgent problem of modern pedagogy. The main goal of the educational system is to educate the younger generation of a creative approach to transform the world around them, active and independent thinking, to contribute the achievement of positive changes in the life of society. The formation of the child's personality serves as a direction of the pedagogical process, which creates favorable emotional conditions for each child, ensures spiritual development and contributes to the formation of artistic and creative abilities of preschool children. The article deals with the problem of the development of children's creativity by means of musical and theatrical art. The importance of cognition of musical art by preschool children is given. The structure of musicality and the ways of its research are revealed. It is noted that the child develops in the process of musical activity under the influence of the values of musical art, communication between music and adults. It was found that listening to music contributes to the development of artistic taste and the formation of value judgments. Exactly music enables the child to see the world around him in a new way because the diverse content of musical works arouses imagination, develops memory, perception, creativity, and enriches vocabulary. The article presents classification of one of the specific types of children's activity. It is theatrical activity associated with dramatization and play, contains a creative principle and is a kind of artistic activity. Theatrical activity reveals the creative potential of the child, fosters a creative personality, teaches the child to notice interesting ideas in the world around him and to impersonate them, to create his own artistic image. It is noted that theatrical-play activity contributes to the child's study of human feelings, fosters will, develops dreams, ideas, initiative of speech, creates a positive attitude, relieves stress, teaches how to solve conflict situations due to play. These types of art education's activities in preschool age form the personality of the child, develop his creative abilities, direct the child's manifestations to evaluative and control actions intuitively.